Design of Web-Based Sales Information System at CV Gemilang Indonesia - Susianawati, Hesty; Tjandrarini, A.B.; Wulandari, Sri Hariani Eko (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
CV. Gemilang Indonesia is a digital printing company and now currently experiencing problems with the company marketings and their business process is still conventional, the second problem is that the company can only accept orders through telephone and on the spot meanwhile the payment confirmation only through calls to the customer and the last problem is internal's problem the owner of the company didn't get the reports per periode to overcome the problems that CV. Gemilang Indonesia, the authors build an online shop application. This application can helps customer to order the products, they no longer have to come to the office to buy the products, they also get the invoice and also can review their history order. This application can also generate sales report for the owner of the company.